The Effect of Intellectual Capital on Financial Performance in the Banking Industry in Indonesia - Hizryan, Fikri (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
In today’s knowledge-based economy, intellectual capital (IC) is increasingly recognized as a strategic asset in the banking sector. This study investigates the impact of IC on the financial performance of Indonesian banks, measured by Return on Assets (ROA). The Modified Value-Added Intellectual Coefficient (MVAIC) model is employed, which includes Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Relational Capital Efficiency (RCE), to assess IC comprehensively. Using panel data regression, the study analyzes financial data from the ten largest banks listed on the Indonesia Stock Exchange over the 2014–2023 period. The findings demonstrate that IC has a significant positive influence on ROA, with HCE and RCE emerging as the most impactful components. Control variables such as firm size, leverage, GDP growth, and inflation (CPI) are included to ensure analytical robustness. This study contributes to the literature by extending the application of the MVAIC model within an emerging market context. The results highlight the critical role of effective IC management in improving bank efficiency, competitiveness, and long-term financial performance. Future research is encouraged to explore the intersection between IC and digital transformation in banking operations.